Analisis Dampak Arabisasi pada Masa Dinasti Umayyah di Timur: Perspektif Sosial dan Politik (661-750 M) - Maysaroh, Maysaroh (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
Arabization, or ta'rib, refers to the process of making something entirely Arabic or as Arabic as possible. This process was integral to the development of Arabic language and culture during the Umayyad Dynasty in the eastern regions. The Arabization movement involved replacing the administrative languages with Arabic; initially, Arabic replaced Greek in the Arab-controlled areas of Damascus, and later, it replaced Persian in Iraq and the eastern provinces. Arabic currency was also introduced during this period. The movement, which reached its culmination during the Umayyad dynasty, had significant impacts on various sectors. Conditions favorable to Arabization were established under Caliph Abdul Malik ibn Marwan, who is considered a key figure in this process. This study employs a historical method with a focus on library research. The analysis relies on historical documents and books regarding Arabization and its effects. The study uses an outline evaluation approach for analyzing the data, guided by a multidimensional theoretical framework. The concept of causality is applied to understand the motivations behind and consequences of the Arabization movement.